Biohydrogen production from real industrial wastewater: Potential bioreactors, challenges in commercialization and future directions. (30th October 2022) - Qyyum, Muhammad Abdul; Ihsanullah, Ihsanullah; Ahmad, Rizwan; Ismail, Sherif; Khan, Amin; Nizami, Abdul-Sattar; Tawfik, Ahmed
Abstract: Hydrogen production potential using real industrial wastewater and recent trends of potential bioreactors by keeping an eye on commercial and economic aspects are presented in this study. A complete explanation of breakthroughs in lab-based and pilot-scale research is provided, demonstrating how different bioreactors and commercialization aspects are poised to be integral in developing sustainable energy. Immobilization, high-loaded reactors, and sequential dark and photo-fermentation are viable methods for implementing and commercializing biohydrogen reactors. This study suggests that microbial electrolytic cell is a more promising technology than others for hydrogen production due to its better control over hydrogen generation rate and effective conversion of organic feedstock regardless of thermodynamic limits. The key challenges to commercial-scale hydrogen production include biomass washout, high operating costs, high energy demand, and complex operation of certain bioreactor systems. Finally, a roadmap is suggested along with future research directions to ensure the sustainable production of hydrogen from wastewater. Highlights: Biological production of hydrogen from various industrial wastewaters is analyzed. Wastewater containing carbohydrates has excellent potential to produce biohydrogen. Key technological challenges are highlighted and recommendations for future research are provided. The economic aspects of existing technologies for biohydrogen production are discussed.